PSYCHOMETRIC ANALYSIS OF PERCEIVED STRESS SCALE AND BRIEF-COPE INVENTORY SCALE IN MENOPAUSAL WOMEN - Masani, Nurul Amirah; Md Mizanur Rahman (Universitas Airlangga, 2024)
Introduction: Menopause is generally considered a stressful experience, with 25% of menopausal women reporting that they experience stress. Using appropriate coping strategies can help reduce stress levels and alleviate other problems in menopausal women. Aims: This study aims to analyze the psychometric properties of two questionnaires designed to measure menopausal stress and coping strategies among menopausal women in Sarawak. Methods: The content validity of this study was assessed by calculating the I-CVI, S-CVI average, S-CVI universal agreement, and CVR. The face validity was also assessed for comparisons within subgroups. A cross-sectional study was conducted in Subis District, Sarawak, involving 221 menopausal women. Participants were selected using a purposive sampling technique and data were collected from face-to-face interviews. Psychometric analysis was performed using SPSS version 28.0. Results: A total of 38 questionnaire items were analyzed by experts for relevance, clarity, simplicity, and ambiguity. After the second modification, the I-CVI, S-CVI/Ave, and CVR for all domains and items were acceptable. Therefore, all items were retained. Face validity was also confimed with an average ICC of 0.979 and a 95% confidence interval between 0.96 and 0.99 (F (9,261a) = 47.996, p < 0.05). Meanwhile, reliability test with a Cronbach's alpha coefficient of greater than 0.70 indicated a good internal consistency. Conclusion: The questionnaires appeared to be a psychometrically sound instrument for measuring menopausal stress and coping strategies in menopausal women.